Posting children’s’ photographs on social networks: Sociological and legal aspects - Kostic, Jelena Ž (Sociološki pregled, 2017)
Posting childrens’ photographs on social networks can be an unsafe activity. Parents are free to choose whether to post photos of their children on-line or not. However, if it is done by a third person or an entity, the question of parental consent comes up to the surface. However, for those situations compulsory consent of both parents is not required by the national legislation in Serbia. Based on content analysis of relevant international documents and legislation, the author argues that in order to prevent potential abuses the already existing solutions need to be improved.
Keywords: underage children; social networks; photographs; parental consent